Investigated on the Rubber Antioxidant 2,2,4-Trimethyl-1,2-dihydroquinoline Polymer - Liu, Yu; Gao, Qingyu; Liu, Lianxin; Li, Shuting (Asian Journal of Chemistry, 2013)
The paper investigated the mechanism of the reaction which are used in synthesis of 2,2,4-trimethyl-1,2-dihydroquinoline and 2,2,4-trimethyl-1,2-dihydroquinoline polymer. Aromatic amines and a-alkenyl alkyl ether condensation of synthetic quinoline and polymerization. one is acetone, aniline on direct condensation to form Schiff base and then further reduced synthesis loop; the other is the first for two molecules of acetone condensation to form iso-propylidene acetone and then iso-propylidene acetone condense with aniline ring. Aniline and acryladehyde will not form Schiff base in acid and directed formed quinoline. Acetone molecules to produce diacetone alcohol, diacetone alcohol shrink generated iso-propylidene acetone. In acidic conditions, iso-propylidene acetone oxygen atoms combine to form hydroxyl and hydrogen ions to form positively charged enol structure. Others aniline and acetone, carried out the nucleophilic addition reaction of N-isopropyl aniline fork. Two molecules of N-isopropyl fork intermediates after addition of aniline, cyclization under acidic conditions, off part of aniline to produce a monomer of 2,2,4-trimethyl-1,2-dihydroquinoline.